Smart Home interface design: An information architecture approach - Hernández Figueroa, Tracy Alexandra (2023)
The usage of IoT devices is rapidly growing. Many users may want to add them to their homes to automate certain tasks, help themselves with information, or monitor their environment continuously. Quick IoT development is taking place on privacy, protocols, and other areas. However, the user interface area is being left out of the efforts. Mobile applications and websites are focused on technical requirements only. Research is not focused on the interaction of the user with the application, so standards and/or tendencies may not be utilized. This investigation aims to implement a smart house application interface focused on the user instead of the technical requirements. To start, the card sorting technique is used to group IoT devices into meaningful groups for users. Then, an interface prototype of a smart house application is created with the feedback obtained from the card sorting activity. Finally, the prototype is evaluated by using a standardized questionnaire.